Optimalisasi UKS dalam Edukasi Kesehatan Reproduksi Remaja di SMP Pertiwi 1 Kota Jambi - Hesty, Hesty; Maimaznah, Maimaznah; Hidayat, Muhammad; Sari, Mila Triana; Kusuma, Ratu (Universitas Baiturrahim, 2025)
Reproductive health is an important aspect in the lives of individuals and communities. Factors that influence reproductive health include social, economic, cultural and environmental. School Health Efforts (UKS) are educational unit efforts to instill, grow, develop and improve healthy living skills. This activity aims to form adolescent cadres who care about reproductive health, increase adolescent knowledge about reproductive health at SMP Pertiwi 1, Jambi City. Junior High School (SMP) is a place of education whose students are teenagers, of course this needs to be equipped with knowledge and motivation related to reproductive health in order to avoid various problems related to reproduction, considering that teenagers are sometimes negligent and less concerned about their reproductive health, seen in the initial study obtained information from the student affairs teacher, this reproductive health problem has not been specifically given, for that it is necessary to form cadres who can be a bridge in providing information related to reproductive health for teenagers. The method of activity is lectures, questions and answers and discussions as well as providing questionnaires for pre-tests and post-tests. This community service was carried out from March 2024 to August 2024. The total number of participants was 10 people. The results of the pre-test and post-test with an average difference of 2-3 points, obtained an increase in knowledge of 26% and the formation of a UKS cadre team which of course will bridge the provision of information related to reproductive health. The output of this community service activity will be published in the Baiturrahim Health Service Journal.